Pathological fire-setting 1951-1991: a review - Barnett, Winfried; Spitzer, Manfred (Medicine, science and the law, 1994)
The purpose of this article is to review the whole literature on pathological fire-setting and related fields since 1951 in order to present a state of the art picture of our contemporary knowledge about this phenomenon. Papers were initially selected by using a Medline search. From the articles obtained in this way the references had to be pursued, because many relevant papers and books in this research field of different scientific and practical disciplines are not listed in conventional literature services. Finally, only those contributions were selected which provided new information when published, by original research, theoretical interpretation or practical implications. The last forty years have brought a growing body of data and understanding--especially concerning pathological fire-setting by children--etiology, and therapy, which often proves successful. The situation remains unclear for arson by psychologically disturbed adults and we still have a poor understanding of arson without apparent motive. There is a conflict of opinion as to whether adult fire-setters are suitable for therapy and therapeutic efforts dealing with psychologically disturbed adults are rare. With increasing knowledge about child fire-setting and its successful treatment, etiological and therapeutic models for adult fire-setting behaviour may be developed. Research into the latter area should focus on both biographical and social conditions of development from childhood on as well as biological measures. Both will be reviewed here.
Gesehen am 09.12.2020